2008
DOI: 10.4012/dmj.27.780
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abrasive particle size on surface properties of flowable composites

Abstract: The purpose of this investigation was to measure and compare both the surface roughness and gloss of flowable composites polished with standardized silicone carbide (SiC) papers. Four flowable and two conventional composites were used in this study. Polymerized specimens were subjected to a polishing procedure comprising 12 sequential steps from coarser to finer grits of SiC paper. At the initial polishing stage, flowable composites were more sensitive to the size of the polishing particles and thus yielded su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 27 publications
4
43
0
2
Order By: Relevance
“…Further, grinding on wet SiC paper bore the additional advantage of a finishing process that was easier to standardize than with rotating instruments. After SiC grinding, the Ra values of the four resin composites tested were in the range of 0.26 to 0.43 µm -similar to the Ra results reported in a previous study using 600-grit SiC as abrasive 28) .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Further, grinding on wet SiC paper bore the additional advantage of a finishing process that was easier to standardize than with rotating instruments. After SiC grinding, the Ra values of the four resin composites tested were in the range of 0.26 to 0.43 µm -similar to the Ra results reported in a previous study using 600-grit SiC as abrasive 28) .…”
Section: Discussionsupporting
confidence: 86%
“…For the Mylar strip-cured surface, the resin-rich surface must be eliminated [29][30][31] ; for the finished surface, it must be polished to obtain a smooth surface texture. In contrast to other studies 28,[32][33][34] where the resin composite specimens were polished after water storage for 24 hours or longer, the dry specimens were finished and polished soon after curing, following the routine clinical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the relatively equal polishing particle size contained in P4000 SiC paper (average particle size 3 µm), and the Sof-Lex (3 µm) and Venus Supra (4-8 µm) systems. These results are in partial agreement with a previous study that suggested surface roughness was comparable when polishing particles less than 12 µm in size were used 30) . Following the toothbrushing cycles, the Z250, Z350, and VEP samples maintained their Ra, while the DUR, KAL, and VED samples showed an increase in Ra.…”
Section: Discussionsupporting
confidence: 83%
“…This demonstrated the effectiveness of the polishing systems in obtaining high gloss on the composite resin surfaces. Smaller polishing particle sizes of < 9 µm as found in these systems can generate improved gloss of composite resin 30) . The small particle size resulted in an increase in gloss units after polishing, while Ra remained stable after polishing.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some difficulties in standardizing the surface of the specimens under laboratory conditions due to the diversity of each material. A previous study 25) stated that polishing using SiC paper with abrasive particles less than 9 µm, rendered a clinically acceptable surface roughness and gloss. Thus, P4000 grit SiC paper was selected in our study to obtain a standard baseline reference point.…”
Section: Discussionmentioning
confidence: 99%